Cooperation and the evolutionary ecology of bacterial virulence: The Bacillus cereus group as a novel study system. (23rd May 2013) - Raymond, Ben; Bonsall, Michael B.
Abstract : How significant is social evolution theory for the maintenance of virulence in natural populations? We assume that secreted, distantly acting virulence factors are highly likely to be cooperative public goods. Using this assumption, we discuss and critically assess the potential importance of social interactions for understanding the evolution, diversity and distribution of virulence in the Bacillus cereus group, a novel study system for microbial social biology. We conclude that dynamic equilibria in Cry toxin production, as well as strong spatial structure and population bottlenecks in hosts are the main ecological factors maintaining the cooperative secretion of virulence factors and argue that collective action has contributed to the evolution of narrow host range. Non‐linearities in the benefits associated with public goods, as well as the lack of private secretion systems in the Firmicutes may also explain the prevalence and importance of distantly acting virulence factors in B. cereus and its relatives. Abstract : The major virulence factors of the B. cereus group are secreted extra‐cellularly. Social conflict between producers and cheats should increase with the metabolic cost and spatial scale of action of virulence factors. We discuss the likely restrictions on cheater fitness and the behavioural ecology of public and private secretion.